2022
DOI: 10.3389/fpls.2022.897795
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponics and elicitation, a combined approach to enhance the production of designer secondary medicinal metabolites in Silybum marianum

Abstract: Medicinal plants have been used to cure human diseases since decades. Silybum marianum, a medicinal plant, is regarded as a source of secondary metabolites with therapeutic value against liver diseases and diabetes. The present study was conducted to enrich the production of secondary metabolites in the vegetative parts of Silybum marianum using elicitation strategy in hydroponic system with different elicitors. The elicitors of fungus Aspergillus niger (0.2 g/L), methyl jasmonate (MeJA) (100 μM) and silver na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…This overall situation leads to a better internal homeostasis culminating into a better phytochemical profile. Similar results have been reported by previous researchers [15][16][17][18][19] in terms of better callus proliferation and callus growth parameters upon elicitation in in vitro culture systems.…”
Section: Agnp and Sa Application Improved Callus Texture Color Compac...supporting
confidence: 91%
See 3 more Smart Citations
“…This overall situation leads to a better internal homeostasis culminating into a better phytochemical profile. Similar results have been reported by previous researchers [15][16][17][18][19] in terms of better callus proliferation and callus growth parameters upon elicitation in in vitro culture systems.…”
Section: Agnp and Sa Application Improved Callus Texture Color Compac...supporting
confidence: 91%
“…This causes a reduction in oxidative stress and can redirect metabolic resources for the production of cell metabolites. Mubeen et al [16] reported similar results for a higher accumulation of flavonoids and phenolics in callus cultures of Silybum marianum by exposing them to silver nanoparticles. Similarly, Bhat and Bhat [15] reported the benefits of elicitation in phenolic accumulation in in vitro cultures of Capsicum sp.…”
Section: Efficacy Of Agnps and Sa In Improving Total Phenolics And Fl...mentioning
confidence: 65%
See 2 more Smart Citations